Bilateral strio-pallido-dentate calcinosis (Fahr's disease): report of seven cases and revision of literature. Issue 1 (December 2016) - Savino, Elisabetta; Soavi, Cecilia; Capatti, Eleonora; Borrelli, Massimo; Vigna, Giovanni; Passaro, Angelina; Zuliani, Giovanni
Abstract Background Fahr's disease is rare a neurodegenerative idiopathic condition characterized by symmetric and bilateral calcifications of basal ganglia, usually associated with progressive neuropsychiatric dysfunctions and movement disorders. The term "Fahr's syndrome" is used in presence of calcifications secondary to a specific cause, but the variability of etiology, pathogenesis, and clinical picture underlying this condition have raised the question of the real existence of a syndrome. Several classifications based on the etiology, the location of brain calcifications and the clinical presentation have been proposed. Here we describe seven clinical cases of basal ganglia calcifications, in order to search for pathognomonic features and correlations between clinical picture and imaging findings. Cases presentation The patients came to our attention for different reasons (most of them for memory/behavior disturbances); all underwent neuro-psychologic evaluation and neuro-imaging. All patients showed variable degrees of deterioration in cognitive function; anxiety and depression were frequent too, and resistant to treatment in all cases. Less frequent, but severe if present, were psychotic symptoms, with different grade of structure and emotional involvement, and always resistant to treatment. We observed only few cases of extrapyramidal disorders related to the disease itself; anyway, mild extrapyramidal syndrome occurred quite frequently after treatment with antipsychotics. Conclusion Based on these findings we discourage the use of the term "Fahr's syndrome", and suggest to refer to Idiopathic or Secondary basal ganglia calcification. Unlike early onset forms (idiopathic or inherited), the clinical presentation of late onset form and Secondary basal ganglia calcification seems to be really heterogeneous. Case–control studies are necessary to determine the actual significance of basal ganglia calcification in the adult population and in the elderly, in cognitive, physical and emotional terms.